2023
DOI: 10.1021/acs.biomac.2c01289
|View full text |Cite
|
Sign up to set email alerts
|

Co-Surfactant-Free Bioactive Protein Nanosheets for the Stabilization of Bioemulsions Enabling Adherent Cell Expansion

Abstract: Bioemulsions are attractive platforms for the scalable expansion of adherent cells and stem cells. In these systems, cell adhesion is enabled by the assembly of protein nanosheets that display high interfacial shear moduli and elasticity. However, to date, most successful systems reported to support cell adhesion at liquid substrates have been based on coassemblies of protein and reactive cosurfactants, which limit the translation of bioemulsions. In this report, we describe the design of protein nanosheets ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…To support the growth of MSCs on scalable bioemulsions, microdroplets stabilised by β-lactoglobulin (βLG) were investigated (Figure 1A) [49]. As this protein is not bioactive, at least from the point of view of integrin ligation and the promotion of cell adhesion, the resulting droplets were further functionalised with RGD peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the growth of MSCs on scalable bioemulsions, microdroplets stabilised by β-lactoglobulin (βLG) were investigated (Figure 1A) [49]. As this protein is not bioactive, at least from the point of view of integrin ligation and the promotion of cell adhesion, the resulting droplets were further functionalised with RGD peptides.…”
Section: Resultsmentioning
confidence: 99%
“…The upper liquid phase was aspirated and replaced with PBS six times. The droplet surface was functionalised as described before [49]. Briefly, sulfo-succinimidyl-4-(N-maleimidomethyl)cyclohexane-l-carboxylate (sulfo-SMCC, Sigma, at a concentration of 2 mg/mL in PBS) were added to the emulsion and kept to react for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This retention in overall globular conformation is an excellent indicator that functionalisation levels should not interfere with self-assembly properties and the ability of corresponding albumins to stabilise emulsions. A globular architecture and striking changes in secondary structure were indeed associated with assembly at liquid-liquid interfaces, including hydrophobic and fluorophilic oil interfaces, and the stabilisation of associated emulsions [25,46,47]. The assembly of functionalised proteins at the surface of the fluorinated oil Novec 7500 was next examined, using interfacial rheology.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, liquid substrates, in the form of oil microdroplets, were proposed to replace solid microcarriers. This has enabled the culture and retention of phenotype of a broad range of cell types, from fibroblasts, keratinocytes and HEK293 cells, to mesenchymal stem cells (MSCs), induced pluripotent stem cells and neural cells [23][24][25][26][27][28]. Underpinning these technologies, it was demonstrated that protein nanosheets self-assembling at corresponding liquid-liquid interfaces and presenting strong interfacial mechanical properties enabled the adhesion, spreading and proliferation of cells [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that CpG needs to enter antigen-presenting cells to perform its biological function, researchers also tried to improve the utilization of CpG by coupling it with antigens [ 30 , 31 ]. At present, many CpG and antigen connectors, such as NHS-PEG n -maleimide (SMCC) and the His-hydrophobic-His (HUH) superfamily of endonucleases, have been explored [ 32 , 33 , 34 ]. Among them, SMCC, which contains an N-hydroxysuccinimide-active ester and maleimide, is used most frequently.…”
Section: Introductionmentioning
confidence: 99%